2020
DOI: 10.4269/ajtmh.19-0631
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Lessons from a Multifaceted National Newborn Program in Solomon Islands: A Mixed-Methods Study

Abstract: Multifaceted interventions are important in improving neonatal quality of care and health outcomes. This study describes the implementation of an intervention to improve the quality of newborn care in Solomon Islands, a small island developing state and lower middle-income country in the Western Pacific. Inputs included training, equipment provision, and healthcare system organizational changes. For evaluation, we used a mixed-methods design, using quantitative (audits of health facility equipment, structure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…A study which assessed the quality of newborn care in five facilities in a neighbouring Pacific island country, the Solomon Islands, found that whilst essential medicines were generally available [ 56 ], other barriers to quality newborn quality care were consistent with those identified in our study including workforce limitations, equipment supply, and lack of infection control measures. A subsequent study by the same research team involved implementation of an intervention to improve the quality of newborn care, specifically through training, equipment provision and health system organisation changes, finding enhanced skills and an improved workplace culture as a result of the training [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study which assessed the quality of newborn care in five facilities in a neighbouring Pacific island country, the Solomon Islands, found that whilst essential medicines were generally available [ 56 ], other barriers to quality newborn quality care were consistent with those identified in our study including workforce limitations, equipment supply, and lack of infection control measures. A subsequent study by the same research team involved implementation of an intervention to improve the quality of newborn care, specifically through training, equipment provision and health system organisation changes, finding enhanced skills and an improved workplace culture as a result of the training [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Equipment such as bag-valve-mask availability can be audited pre-and post-course, including after an Early Essential Newborn course in Solomon Islands (Tosif et al 2020) and a Service Availability and Readiness Assessment pre-and post-HBB in Rwanda (Umunyana et al 2020). A large study involving 13,169 participants at HBB courses in Tanzania performed 335 facility and equipment checklists to determine whether, for example, a bag-valve-mask and suction devices were present in every delivery area (Arlington et al 2017).…”
Section: Kirkpatrick Level Four 'A'mentioning
confidence: 99%